Menganalisi Daya Tarik Cafe Mbah Dharmo Ambarawa: Peran Harga, Promosi dan Kualitas Produk Dalam Keputusan Pembelian - Saputra, Ari; Suryatama, Fajar; Rakhman, M. Arif (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The purpose of this study was to examine the impact of price, advertising, and product quality on customer purchasing decisions for Mbah Dharmo Ambarawa Cafe. With increasing competition in the culinary industry, business owners need to understand the factors that drive consumer decisions when choosing a product or service. This study uses a quantitative approach with measurement methods for 100 respondents selected using targeted sample technology. Data were analysed using SmartPLS 3.0 software using minimal structural equation modelling (PLS-SEM). The results showed that product quality has a significant positive impact on purchasing decisions, while not significantly affecting price and advertising campaigns. The implications of these findings suggest that improving product quality is an important factor for customer attraction and retention. Therefore, Cafe Mbah Dharmo recommends that we continue to maintain our product quality and consistency standards to increase customer satisfaction.